Controlling Stunting Prevalence Through Health Function Budgeting: The Role of APIP and Educational Factor in Indonesia - Setiawan, Moh. Hedar; Furqan, Andi Chairil; Djuri, Phatra Anggana; Din, Muhammad (Akuntansi: Jurnal Akuntansi Integratif, 2026)
Purpose: This study aims to examine the effect of health function expenditure on the reduction of stunting prevalence, with the effectiveness of Government Internal Supervisory Apparatus (APIP) as a moderating variable and average years of schooling as a control variable. Methodology/approach: This study employs a quantitative approach using secondary panel data from local governments in Indonesia for the 2021–2022 period, comprising 518 and 1,036 observations. The data are sourced from Statistics Indonesia (BPS), Bappenas, and the Financial and Development Supervisory Agency (BPKP) And use Panel data regression analysis. Findings: The results indicate that health function expenditure, APIP maturity, and mean years of schooling have a negative and significant effect on stunting prevalence. However, APIP, as a moderating variable, does not strengthen the relationship between health expenditure and stunting reduction. Instead, the interaction term shows a positive coefficient, indicating that the moderating effect does not support the proposed hypothesis. This suggests that APIP oversight remains largely administrative rather than performance-oriented. Practical implications: These findings highlight the need to improve the effectiveness of health budget allocation, strengthen APIP competencies in performance-based auditing, and enhance nutrition, public health, and education quality. Originality/value: This study contributes to the literature by examining APIP as a moderating variable between public health expenditure and stunting reduction, with educational attainment as a control variable. Using recent Indonesian panel data, the study provides empirical evidence on the governance of health spending effectiveness.